2021
DOI: 10.1111/bcp.15055
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of roxadustat for anaemia in dialysis‐dependent and non‐dialysis‐dependent chronic kidney disease patients: A systematic review and meta‐analysis

Abstract: Aims Renal anaemia is a common complication of chronic kidney disease (CKD). Roxadustat is the first‐in‐class oral hypoxia‐inducible factor prolyl hydroxylase inhibitor for the treatment of anaemia. In this systematic review, we aimed to investigate the efficacy and safety of roxadustat in the treatment of anaemia in CKD patients. Methods PubMed, Cochrane Library, Embase, and http://ClinicalTrials.gov databases were searched from their inception to February 2021 for randomised controlled trials (RCTs) that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…Third, recent meta-analysis indicated that standarddose roxadustat therapy could increase serious incidences of treatment-emergent adverse events compared with ESA in non-dialysis-dependent CKD population. 25,26 Taken together, more heterogeneous and long-term interventional studies should be performed to observe the effectiveness and safety of different initial-dose regimens and dosing-adjustment strategies for anemia correction.…”
Section: Discussionmentioning
confidence: 99%
“…Third, recent meta-analysis indicated that standarddose roxadustat therapy could increase serious incidences of treatment-emergent adverse events compared with ESA in non-dialysis-dependent CKD population. 25,26 Taken together, more heterogeneous and long-term interventional studies should be performed to observe the effectiveness and safety of different initial-dose regimens and dosing-adjustment strategies for anemia correction.…”
Section: Discussionmentioning
confidence: 99%
“…Daprodustat may better influence DD-CKD patients' optimizing iron metabolism [18], and is not inferior to ESAs regarding ΔHb and cardiovascular diseases [31]. Nevertheless, some literature proposed that safety data of HIF-PHIs like Roxadustat is still emerging, and attention must be poured into the risk of TEAE, especially SAEs during therapy [42,52]. The above research is basically limited to studying a specific drug in HIF-PHI, and the safety is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, this drug is not yet widely used in clinical practice and is associated with a risk of serious adverse events; for example, it can increase the prevalence of infections and cardiac, vascular, hematologic and lymphatic diseases. 8 In addition, 16% of patients show poor response. 9 Renal anaemia is still a refractory disease for which it is imperative to find new therapeutic targets and develop new therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%